2003
DOI: 10.1002/ejoc.200200580
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of Polyethylated Aromatic Systems

Abstract: Hexaethylbenzene adopts a conformation with the ethyl groups perpendicular to the aromatic ring and oriented in a fully alternated up‐down arrangement. The synthesis, stereochemistry and rotational barriers of systems possessing two polyethylaryl rings in spatial proximity (e.g., decaethylbiphenyl, octaethylbiphenylene) are reviewed. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2003)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 90 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…We were interested to know whether this design concept could be extended to larger aromatic systems, such as biphenylenes. The X-ray crystal structure of octaethylbiphenylene revealed that this compound adopts an ababbaba conformation in the solid state rather than the fully alternating abababab conformation that was calculated to be the most stable (Taha et al, 2000;Marks et al, 2003). However, we previously prepared the new eight armed ligand octakis(2-pyridylmethylsulfanyl)biphenylene and were encouraged to find that in the solid state it was preorganized into the fully alternating abababab conformation (McMorran & Steel, 2003).…”
mentioning
confidence: 99%
“…We were interested to know whether this design concept could be extended to larger aromatic systems, such as biphenylenes. The X-ray crystal structure of octaethylbiphenylene revealed that this compound adopts an ababbaba conformation in the solid state rather than the fully alternating abababab conformation that was calculated to be the most stable (Taha et al, 2000;Marks et al, 2003). However, we previously prepared the new eight armed ligand octakis(2-pyridylmethylsulfanyl)biphenylene and were encouraged to find that in the solid state it was preorganized into the fully alternating abababab conformation (McMorran & Steel, 2003).…”
mentioning
confidence: 99%